PENGARUH PERBEDAAN VARIETAS DAN STARTER PADA SILASE TEBON JAGUNG TERHADAP KADAR ABU, KADAR LEMAK KASAR, DAN KADAR BAHAN EKSTRAK TANPA NITROGEN - Neily Zulfa Umala, Farida Fathul, Agung Kusuma Wijaya dan Liman (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2020)
This study aimed to investigate the content of ash, ether extract, and nitrogen free extract in corn silage with two varieties (BISI-18 and NK-212) given two types of starter (molasses and rice bran). This research was conducted in May-August 2019 at the Laboratory of Animal Nutrition and Feed, Department of Animal Husbandry, Faculty of Agriculture, University of Lampung. The factors studied were (1) corn stover varieties which consisted of two varieties (BISI-18 and NK-212) and (2) starter which consisted of two types of starter (molasses and rice bran). The results of this study showed that there was no interaction (P>0.05) between the use of varieties of corn forage and starter on ash, ether extract, and nitrogen free extract of silage. The use of different corn varieties had a significant effect (P<0.05) on silage ash, but it had no significant effect (P>0.05) on ether extract and nitrogen free extract of silage. The use of different types of starter has no significant effect (P>0.05) on ash, ether extract and nitrogen free extract of silage. Keywords: Corn Silage, Silage Nutrition, Starter, Varieties